Language Dominance Affects Bilingual Performance and Processing Outcomes in Adulthood - Puig-Mayenco, Eloi; Cunnings, Ian; Bayram, Fatih; Miller, David; Tubau, Susagna; Rothman, Jason (Frontiers in Psychology, 2018)
This study examines the role of language dominance (LD) on linguistic competence outcomes in two types of early bilinguals: (i) child L2 learners of Catalan (L1 Spanish-L2 Catalan and, (ii) Child Spanish L2 learners (L1 Catalan-L2 Spanish). Most child L2 studies typically focus on the development of the languages during childhood and either focus on L1 development or L2 development. Typically, these child L2 learners are immersed in the second language. We capitalize on the unique situation in Catalonia, testing the Spanish and Catalan of both sets of bilinguals, where dominance in either Spanish or Catalan is possible. We examine the co-occurrence of Sentential Negation (SN) with a Negative Concord Item (NCI) in pre-verbal position (Catalan only) and Differential Object Marking (DOM) (Spanish only). The results show that remaining dominant in the L1contributes to the maintenance of target-line behavior in the language.